Roles of Gut Microbial Metabolites in Diabetic Kidney Disease - Fang, Qing; Liu, Na; Zheng, Binjie; Guo, Fei; Zeng, Xiangchang; Huang, Xinyi; Ouyang, Dongsheng (Frontiers in Endocrinology, 2021)
Diabetes is a highly prevalent metabolic disease that has emerged as a global challenge due to its increasing prevalence and lack of sustainable treatment. Diabetic kidney disease (DKD), which is one of the most frequent and severe microvascular complications of diabetes, is difficult to treat with contemporary glucose-lowering medications. The gut microbiota plays an important role in human health and disease, and its metabolites have both beneficial and harmful effects on vital physiological processes. In this review, we summarize the current findings regarding the role of gut microbial metabolites in the development and progression of DKD, which will help us better understand the possible mechanisms of DKD and explore potential therapeutic approaches for DKD.